THE ADULT-CHILD DYAD AS A PROBLEM-SOLVING SYSTEM: AN EXPERIMENT WITH ONE BILINGUAL INDONESIAN CHILD - Rentauli Mariah Silalahi (Universitas Pelita Harapan, 2021)
This study tries to reveal how the transition from interpsychological to intrapsychological functioning happens in an adult-child dyad’s activity involving a 3.6 year-old-child and the child’s mother. The study explores how the adult and child divided up the strategic responsibilities for carrying out a problem-solving task of completing a puzzle. The experiment, which took place in the child’s living room and lasted for 48 minutes, was videotaped and observed while all utterances by the adult and child were transcribed verbatim. Coding was done in order to note information showing the gaze behavior, interventions from the adult, and episodes for each correct match. Thematic analysis was chosen as the method to analyze the transcripts in order to find meaningful patterns. The study found that the adult’s intervention is important in the early stage of the joint-problem activity while, when the child takes more responsibility and develops some strategies as the child becomes more self-regulated, the adult’s role in scaffolding decreases. There is a transition from the interpsychological to intrapsychological functioning in the adult-child dyad while gazes towards the played cards outweigh the role of gazes towards other objects.